2005
DOI: 10.1371/journal.pmed.0020284
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Immune Cells in Axillary Lymph Nodes Predicts Disease-Free Survival in Breast Cancer

Abstract: BackgroundWhile lymph node metastasis is among the strongest predictors of disease-free and overall survival for patients with breast cancer, the immunological nature of tumor-draining lymph nodes is often ignored, and may provide additional prognostic information on clinical outcome.Methods and FindingsWe performed immunohistochemical analysis of 47 sentinel and 104 axillary (nonsentinel) nodes from 77 breast cancer patients with 5 y of follow-up to determine if alterations in CD4, CD8, and CD1a cell populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
160
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(171 citation statements)
references
References 36 publications
9
160
1
1
Order By: Relevance
“…8 Similar to another group, 9 we also did not detect any differences in Foxp3 þ cells between sentinel lymph nodes groups. Unlike our findings, two other groups have reported increases in Foxp3 þ cells in melanoma-involved lymph nodes compared with those without metastasis, 10,11 which is similar to results reported in breast cancer.…”
Section: Discussionsupporting
confidence: 82%
“…8 Similar to another group, 9 we also did not detect any differences in Foxp3 þ cells between sentinel lymph nodes groups. Unlike our findings, two other groups have reported increases in Foxp3 þ cells in melanoma-involved lymph nodes compared with those without metastasis, 10,11 which is similar to results reported in breast cancer.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, the relative abundance of immunosuppressive T‐regulatory cells (Tregs) (Bates et al., 2006; Pages et al., 2010) or CD4 + effector T‐cells (Denardo et al., 2011; Kohrt et al., 2005; Zhou et al., 2009) can be prognostic of comparatively poor outcome, as can the abundance of various myeloid cell types, including macrophages, neutrophils and immature myeloid cells (Qian and Pollard, 2010; Steidl et al., 2011; Zhou et al., 2009), a subset of which are referred to as myeloid‐derived suppressor cells on account of their ability to inhibit T‐cell functions (Sica and Bronte, 2007). Furthermore, studies in mouse models of cancer have revealed that profuse myeloid cell infiltration correlates with resistance to antiangiogenic therapies targeting the VEGF‐signaling axis (Bergers and Hanahan, 2008; Ferrara, 2010; Squadrito and De Palma, 2011), or accelerated tumor re‐growth following local tumor irradiation (Ahn and Brown, 2008; Kioi et al., 2010; Kozin et al., 2010).…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…High percentages of CD4 þ T cells in primary breast cancers positively correlate with markers of disease progression, including metastatic spread to sentinel lymph nodes and increased primary tumor size (Chin et al 1992;Kohrt et al 2005). The extent of T-cell infiltration into invasive breast carcinomas has been reported to range from 1% -45% of the total cellular mass (Chin et al 1992).…”
Section: T Lymphocytes and Breast Cancermentioning
confidence: 99%
“…However, the exact composition of T-lymphocyte infiltration varies greatly and may profoundly affect disease progression and overall patient survival. Perhaps more significant, the ratio of CD4 þ to CD8 þ T cells or T H 2 to T H 1 cells present in primary tumors, where CD4 þ or T H 2 cells are more frequent than CD8 þ or T H 1 cells, correlates with lymph node metastasis and reduced overall patient survival (Chin et al 1992;Kohrt et al 2005). More recently, unsupervised expression profiling from breast cancer-associated stroma revealed a gene signature predictive of good prognostic outcome (.98%, 5-year survival) that was functionally enriched for elements of a T H 1-type immune response, including genes suggestive of cytotoxic T lymphocyte (CTL) and natural killer (NK) cell activity (Finak et al 2008).…”
Section: T Lymphocytes and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation